A critical review of discrete filled function methods in solving nonlinear discrete optimization problems - Woon, Siew Fang; Rehbock, Volker (Elsevier Ltd., 2010)
Many real life problems can be modeled as nonlinear discrete optimization problems.Such problems often have multiple local minima and thus require global optimization methods.Due to high complexity of these problems, heuristic based global optimization techniques are usually required when solving large scale discrete optimization or mixed discrete optimization problems.One of the more recent global optimization tools is known as the discrete filled function method.Nine variations of the discrete filled function method in literature are identified and a review on theoretical properties of each method is given.Some of the most promising filled functions are tested on various benchmark problems.Numerical results are given for comparison.